Edukasi Tentang Pendewasaan Usia Perkawinan Pada Kelompok Pusat Informasi dan Konseling Remaja di Kota Bontang: Education about Maturing Marriage Age in the Youth Information and Counseling Center Group in Bontang City - Indah, Sekar Nurhidayah; Paramitha, Devy Indah; Rukmana, Gilang Mukti (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
The still high rate of early childhood marriage is a challenge for the East Kalimantan government, especially in Bontang City. Based on data from the Public Relations of the Bontang Religious Court, there were 31 requests for marriage dispensation in Bontang City in 2022. This community service aims to inform people about the age of marriage and provide awareness about the dangers of marriages performed below the ideal age. In collaboration with the Bontang City Indonesian Genre Forum under the auspices of the Bontang City Women's Empowerment and Family Planning Service, community service activities were carried out by providing counseling and attended by 33 participants representing the Bontang City Youth Information and Counseling Center (PIK) Group. It is hoped that the results of this activity will broaden participants' understanding of the ideal age limit for marriage and the potential problems that will arise from early marriage.